The earthly reapers: Investigating funeral businesses’ persuasive techniques used to convince Filipinos for advanced death planning - Payo, Elsa Mae; Palana, Princess Zyra; Bajade , Princess Thea; Relevo, Shawn Michael; Nacionales, Joseph; Claridad, Norberto (Journal of Language, Literature, Social and Cultural Studies, 2023)
Death is a biological phenomenon that we cannot control. It might happen at any moment and in any place. In other words, we cannot predict when it will occur, hence, death is imminent. On the one hand, one might say that life is all one has and that the prospect of losing it is the greatest loss one can endure but the question that arises is, how prepared are you for that big day? Have you already come up with an approach yet? A life insurance plan offers advanced death care planning, and they present a lot of good causes for availing their death care plans. But how did they manage to persuade their clients? Thus, this study aims to gain insight into the persuasive tactics used by death care planners to convince their clients. How can the agents of a life plan service meet the needs of clients who wish to acquire life plans, and incredibly advanced death care plans? This study uncovered some of the challenges that death care planners encounter when convincing people to use their services. This study uses a qualitative research design with the help of Interpretative Phenomenological Analysis (IPA) in its implementation. Braun and Clarke's thematic analysis was utilized for data analysis. Seven participants were selected to provide relevant conclusions about the approaches of Appealing to the Client's Emotion, Appealing to Facts, Comparing Plan-holders and Non-Plan Holders, Creating an Impact on the Client's Perspective, Financial Incapacity hinders people from Availing of Death Planning, Not Part of Clients’ Priorities, and Death Planning Violates their Traditional Belief.